Samuel Johnson and the culture of property - Hart, Kevin, 1954- (Cambridge, U.K. ; New York : Cambridge University Press, 1999)
Kevin Hart traces the vast literary legacy and reputation of Samuel Johnson. Through detailed analyses of the biographers and critics who preserved Johnson's life for posterity, Hart explores the emergence of 'The Age of Johnson', and demonstrates how Johnson came to occupy a central place in the English literary canon.
The monument -- 'The age of Johnson' -- Property lines -- Subordination and exchange -- Cultural properties -- Everyday life in Johnson -- Conclusion : 'property, contract, trade and profits'.
Includes bibliographical references (pages 223-241) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Johnson, Samuel, -- 1709-1784 -- Knowledge -- Economics; Boswell, James, -- 1740-1795.; Johnson, Samuel, -- 1709-1784; Life of Samuel Johnson (Boswell, James); Property -- Social aspects -- Great Britain -- History -- 18th century; Literature and society -- Great Britain -- History -- 18th century; Intellectual property -- Great Britain -- History -- 18th century; Cultural property -- Great Britain -- History -- 18th century; Great Britain -- Civilization -- 18th century; Biography as a literary form; Economics in literature; Biography; Biographies as Topic; Littérature et société -- Grande-Bretagne -- Histoire -- 18e siècle.; Propriété intellectuelle -- Grande-Bretagne -- Histoire -- 18e siècle.; Grande-Bretagne -- Civilisation -- 18e siècle.; Biographie (Genre littéraire); Économie politique dans la littérature.; Biographies; Patrimoine culturel immatériel -- Grande-Bretagne -- Histoire -- 18e siècle.; biographies (literary genre); biography (general genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Biography as a literary form; Civilization; Cultural property; Economics; Economics in literature; Intellectual property; Literature and society; Property -- Social aspects; Great Britain; 1700-1799; History